Effectiveness, Efficiency of Spending and Health Office Strategy in Overcoming Stunting in Maluku - Faisal Tappa; Stellamaris Metekohy; Isaac Tony Matitaputty; Fahrudin Ramly (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
The stunting rate in Maluku has increased from 2016 to 2018. This prompted the local government to issue a handling policy. The consequence is the budget allocation to accelerate the reduction of stunting rates. However, appropriate strategies are also needed to achieve this goal so that the existing budget is used effectively and efficiently. This study first aims to analyze the level of expenditure variance, expenditure growth, expenditure effectiveness and efficiency. Second, to describe the progress of stunting handling and recommend priority strategies in the prevention. This research uses a mixed-method approach with a type of concurrent triangulation design. Quantitative data is obtained from financial reports and questionnaires, while qualitative data is obtained through interviews, documents and field notes during the study. After the data was collected, variance, growth, effectiveness and efficiency of expenditure and strategy analysis were conducted. The results showed that the budget for handling stunting in the health Office fluctuates yearly but tends to decrease. The variance of expenditure is classified as good, as well as the effectiveness of expenditure is still quite good. Expenditures for handling stunting are also very efficient, which reduces the stunting rate. This can be seen in the stunting rate 2019 of 30.38 to 26.10 in 2022.